2017
DOI: 10.1177/0145721717714894
|View full text |Cite
|
Sign up to set email alerts
|

Resilience-based Diabetes Self-management Education: Perspectives From African American Participants, Community Leaders, and Healthcare Providers

Abstract: Purpose The purpose of this qualitative, focus group study was to further refine the Resilience-based Diabetes Self-management Education (RB-DSME) recruitment process and intervention, build greater trust in the community, and identify strategies to enhance its sustainability as a community-based intervention in African American church settings. Methods Six 2-hour focus groups (N = 55; 10 men and 45 women) were led by a trained moderator with a written guide to facilitate discussion. Two sessions were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…34 For African Americans in particular, peer support groups provide a culturally sensitive safe space to vent about the frustration of managing T2DM day in and day out as well as learn from others. Participants’ expressed desire for culturally sensitive diabetes support resources closely mirror findings in a recent focus group study by Lehrer and colleagues, 35 where African American participants of a resilience-based diabetes education program highlighted the benefits of interacting with similar others in support groups. Similar to the current study, participants in the Lehrer et al 35 study indicated that African American peer support groups provide an empathetic environment, where attendees are reminded that others also live with T2DM and face similar difficulties when it comes to managing the condition.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…34 For African Americans in particular, peer support groups provide a culturally sensitive safe space to vent about the frustration of managing T2DM day in and day out as well as learn from others. Participants’ expressed desire for culturally sensitive diabetes support resources closely mirror findings in a recent focus group study by Lehrer and colleagues, 35 where African American participants of a resilience-based diabetes education program highlighted the benefits of interacting with similar others in support groups. Similar to the current study, participants in the Lehrer et al 35 study indicated that African American peer support groups provide an empathetic environment, where attendees are reminded that others also live with T2DM and face similar difficulties when it comes to managing the condition.…”
Section: Discussionsupporting
confidence: 59%
“…Participants’ expressed desire for culturally sensitive diabetes support resources closely mirror findings in a recent focus group study by Lehrer and colleagues, 35 where African American participants of a resilience-based diabetes education program highlighted the benefits of interacting with similar others in support groups. Similar to the current study, participants in the Lehrer et al 35 study indicated that African American peer support groups provide an empathetic environment, where attendees are reminded that others also live with T2DM and face similar difficulties when it comes to managing the condition. Participants in the current study also emphasized the importance of offering gender-specific support groups, a request primarily voiced by male focus group participants where they noted that men and women might experience distinctly different T2DM stressors that affect their mental health.…”
Section: Discussionsupporting
confidence: 59%
“…As African Americans are more likely to have a lower quality of life due to pain [39], and less likely to receive care for chronic pain [21], interventions aimed at improving coping strategies and healthcare access may specifically benefit African Americans. Community involvement and church-based self-management programs have been effective in improving health outcomes and wellbeing among African Americans [26, 50]. Several strategies have also been developed to target healthcare providers’ racial bias when caring for African Americans with pain, including perspective-taking [14], and shared decision-making [13, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Each FGD comprised 2 to 5 HCPs and lasted approximately 65-100 minutes. A discussion guide was developed based on existing literature ( 33 36 ) and the study team’s expertise and pilot tested. The guide incorporated open-ended questions on different aspects of diabetes management.…”
Section: Methodsmentioning
confidence: 99%
“…Each FGD comprised 2 to 5 HCPs and lasted approximately 65-100 minutes. A discussion guide was developed based on existing literature (33)(34)(35)(36) and the study team's expertise and pilot tested.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%